YqhG is required for systemic virulence but not for in vitro growth. - Jianhua Liao (1393228) (2025)
(A) Growth curves of MRSA wild-type (WT), ΔyqhG mutant, and complemented strain (ΔyqhG-C) cultured in TSB at 37 °C with shaking. (B) Kaplan–Meier survival analysis of BALB/c mice (n = 10 per group) following intravenous infection with 2 × 10⁷ CFU of each strain. (C-F) Bacterial burden in the heart (C), kidney (D), liver (E) and spleen (F) at 24 h post-infection. CFU were enumerated from homogenized tissues. Data represent at least three independent experiments. Statistical analyses were performed using one-way ANOVA (C-F) and log-rank test (B). *P < 0.05, **P < 0.01, ***P < 0.001.